Scrubber: A potentially overestimated compliance method for the Emission Control Areas: The importance of involving a ship's sailing pattern in the evaluation. (August 2017) - Gu, Yewen; Wallace, Stein W.
Highlights: The scrubber is overestimated if operational behavior changes are not considered. The overestimation of scrubber can lead to wrong decision and substantial loss. The port call density in ECA affects the emission control choice. A route with high port call density in ECA favours scrubber. Fuel-switching is preferred in the loop with low port call density in ECA. Abstract: Different methods for sulphur emission reductions, available to satisfy the latest Emission Control Areas (ECA) regulations, may lead to different sailing patterns (route and speed choices of a vessel) and thus have significant impact on a shipping company's operating costs. However, the current literature does not include sailing pattern optimization caused by ECA, and its corresponding cost effects, in the evaluation and selection process for sulphur abatement technology. This leads to an inaccurate estimation of the value of certain technologies and hence an incorrect investment decision. In this paper, we integrate the optimization of a ship's sailing pattern into the lifespan cost assessment of the emission control technology, so that such expensive and irreversible decisions can be made more accurately. The results shows that a considerable overestimation of the value of scrubbers, and thus a substantial loss, can occur if the sailing pattern of a ship is not considered in the decision-making process. Furthermore, we also illustrate that it is more important to involve a ship's sailing pattern when the port call density inside ECA is low.